2013
DOI: 10.1186/1471-2164-14-291
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gene expression in Caenorhabditis elegans associated with organophosphate pesticide intoxication and recovery

Abstract: BackgroundThe principal toxicity of acute organophosphate (OP) pesticide poisoning is the disruption of neurotransmission through inhibition of acetylcholinesterase (AChE). However, other mechanisms leading to persistent effects and neurodegeneration remain controversial and difficult to detect. Because Caenorhabditis elegans is relatively resistant to OP lethality—particularly through the inhibition of AChE—studies in this nematode provide an opportunity to observe alterations in global gene expression follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Based on the results of the present study, the resistance of M. incognita to fosthiazate has been circumstantiated in tomato greenhouse, where chemical pest control strategies have been used for at least 7 years; however, the underlying molecular mechanism remains poorly understood. The fosthiazate-resistant population exhibited lower levels of AChE activity than the susceptible population, suggesting that a modified AChE might contribute to the reduced substrate affinity1721. RNAi results further confirmed that the ace 2 gene plays a major role in the interaction of AChE and fosthiazate, although mutation of ace 2 did not affect nematode infection.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Based on the results of the present study, the resistance of M. incognita to fosthiazate has been circumstantiated in tomato greenhouse, where chemical pest control strategies have been used for at least 7 years; however, the underlying molecular mechanism remains poorly understood. The fosthiazate-resistant population exhibited lower levels of AChE activity than the susceptible population, suggesting that a modified AChE might contribute to the reduced substrate affinity1721. RNAi results further confirmed that the ace 2 gene plays a major role in the interaction of AChE and fosthiazate, although mutation of ace 2 did not affect nematode infection.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, mutations in at least 18 Caenorhabditis elegans genes were shown to confer resistance to the OP-like carbamate pesticide aldicarb20. Alterations of gene expression in C. elegans were found to be associated with organophosphate pesticide intoxication and recovery21. Class C of acetylcholinesterase of Meloidogyne had high affinity for acetylcholine, but was highly resistant to carbamate and organophosphate inhibitors2223.…”
mentioning
confidence: 99%
“…This aspect reinforces the concept that there must be other substances or chemicals in the water samples that were not detected a priori but even so exert weighty toxicological effects. Several reports showed that C. elegans was sensitive to different substances such as pesticides, heavy metals and toxins (Höss et al, 2013;Jiang et al, 2016;Lewis et al, 2013;Negga et al, 2011;Ruan et al, 2009;Yunhui et al, 2009). So it is possible that C. elegans toxicity could be explained by pollutants derived from the anthropogenic activities developed in the area (like agriculture, livestock and recreations).…”
Section: Multivariate Linear Model and Simple Regression Of Relative mentioning
confidence: 97%
“…Finally, we tested a new context-centric prediction method, ‘find context-associated hub genes’, using toxicogenomics data derived from the exposure of C. elegans to the organophosphate pesticide, dichlorvos (17). The principle mechanism of acute toxicity by organophosphate pesticide is the inhibition of acetylcholinesterase.…”
Section: Case Studiesmentioning
confidence: 99%
“…We therefore conducted an analysis with 32 up-regulated genes (defined by >1.5-fold increase of expression levels after 26 h) and identified gene C14C10.1, which is a putative mitochondrial carrier protein, as the top candidate gene associated with prolonged intoxication by dichlorvos. Mitochondrial dysfunction has been suggested as a mechanism of intoxication (17) and many human diseases, such as metabolic disorders, neurodegenerative diseases, and muscle dystrophy, are associated with mutations of the mitochondrial carrier proteins (18). C14C10.1 may therefore represent a potential target for dichlorvos.…”
Section: Case Studiesmentioning
confidence: 99%